PEMANFAATAN RADIO FREQUENCY IDENTIFICATION (RFID) UNTUK SISTEM ABSENSI PEGAWAI - Joko Christian; Hamdi Nasrullah (Universitas Budi Luhur, 2013)
The rapid development of information technology has enabled the fulfillment of industrial demands which will operate with a high level of efficiency. The use of information technology in the industry is in managing the human resources, they able to manage data capture process, information processing, and process to calculate the remuneration. Specifically for attandence process capture data, we can be used biometric technology, or smart card technology. Biometric technology is the best option in terms of the data validity, but unfortunately, not every organization has sufficient funds to adopt a biometric attendance system. In solving this problem, this study will develop an attendance system that is cost effective, thus become more attractive for the small and medium organizations to adopt this system. Based on RFID technology, the system requires an RFID starter kit connected to a computer as a terminal. The process of employee attendance capture can be done efficiently, if just put the RFID card close to the RFID card reader. The system is also designed to support the employee shift system and the report of employee absences, increasing the effectiveness of human resources data processing to calculate the employee of remuneration. The system is expected to be an alternative solution for small and medium sized organizations to improve the quality of human resources.Keywords : RFID starter kit, RFID ID-12, employee attendance system